Morphology of a Breached Embankment Due to Overtopping Flow - Mohamed Yusof, Zainab; Abd. Wahab, Ahmad Khairi; Ismail, Zulhilmi; Amerudin, Shahabuddin (International Journal of Integrated Engineering, 2021)
An embankment is a man-made hydraulic structure, is built to provide flood control. It also presents risks to property and life due to their potential to fail and causes catastrophic flooding. In order to mitigate these risks, authorities and regulators need to carefully analyse and inspect embankment dams to identify potential failure modes and protect against them. This paper presents embankment failure morphology and the amount of erosion due to overtopping flow. The breached morphology is analysed for an embankment slope of 1V:3H. The embankment is constructed in the laboratory using a medium sand grain size of non-cohesive soil. The dimension of embankment height is 0.1 m and has been tested with inflows rate of Q = 0.8 Ã—10-3 m3/s. Experimental results showed that the breached peak discharge is influenced by the morphology of the sediment eroded. The volume loss calculation of the embankment erosion is calculated using SURFER 8, indicating the volume of 0.0079 m3 with the peak breached discharge of 3.63 Ã—10-3 m3/s, respectively.